Mitigating Private Infrastructure Project Risks - Audu, Ejura Phoebe (International Finance Corporation, Washington, DC, 2018)
Private sector financing is essential to bridging the infrastructure gap between emerging markets and developed countries. Given the risk profiles of many of these projects, however, private investors are reluctant to help finance important infrastructure investments. Now, new packages of financial and advisory products offered by development finance institutions are substantially improving these risk profiles, making them viable for private investment even in very challenging environments. The revenue and risk profiles of emerging market infrastructure projects present major challenges to attracting much needed private investment. Without private financing, however, many of these infrastructure projects, which are critical to meeting development goals, will not be built. Recognizing this gap, development institutions have created new financial products that lower the risk of emerging market infrastructure projects for private investors. As recent projects in Nigeria and Cote d’Ivoire demonstrate, this new approach can help attract private investment to even the most challenging environments.